(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study analyzes news discourse concerning trilateral cooperation between Qatar, Saudi Arabia, and the United Nations (UN) in providing financial support to the Syrian government to pay civil servants’ salaries for a three-month period. The analysis employs Teun A. van Dijk’s Critical Discourse Analysis framework, which encompasses three dimensions: textual structure, social cognition, and social context. The study examines news reports from Al Jazeera and RT entitled Qatar, Saudi Arabia, and the United Nations Sign an Agreement to Support the Syrian Government. The findings indicate that at the macrostructural level, the news frames the cooperation as an expression of Arab solidarity and a humanitarian effort. The superstructure of the news is deductive and systematic, while the microstructure reveals language choices that are neutral, formal, and humanistic. At the level of social cognition, journalists and media institutions such as Al Jazeera and Russia Today process the event based on humanitarian values, Islamic solidarity, and the diplomatic interests of Qatar and Saudi Arabia. Meanwhile, in the social context dimension, the news text is closely connected to global power dynamics and ideologies that signify the emergence of Gulf states as actors in regional stabilization. Overall, the news functions as an instrument of soft power and geopolitical legitimation through narratives of humanitarianism and development.